Cardiorespiratory Fitness Associates with Metabolic Risk Independent of Central Adiposity - Silva, G.; Aires, L.; Martins, C.; Mota, J.; Oliveira, J.; Ribeiro, J. C. (International Journal of Sports Medicine, 2013)
This study sought to analyze the associations between cardiorespiratory fitness (CRF), waist circumference (WC) and metabolic risk in children and adolescents. Participants were 633 subjects (58.7% girls) ages 10–18 years. Metabolic risk score (MRS) was calculated from HDL-cholesterol, triglycerides, fasting glucose and mean arterial pressure. MRS was dichotomized into low and high metabolic risk (HMRS). CRF was defined as the maximal oxygen uptake (VO2max) estimated from the 20 m Shuttle Run Test. The first quartile of CRF was set as the low fitness group. The fourth quartile of WC was defined as high central adiposity. With adjustments for age, sex and WC, CRF was correlated with MRS (r=−0.095; p<0.05). WC was correlated with MRS (r=0.150; p<0.001) after adjustments for age, sex and CRF. Participants who had low fitness levels, presented higher levels of MRS (p<0.001) compared to those who were fit, even after adjustment for age, sex and WC. In comparison with subjects who were fit with normal central adiposity, an increased odds ratio (OR) for being at HMRS was found for participants who were of low fitness level with high central adiposity (OR=2.934; 95%CI= 1.690–5.092) and for those who were of low fitness with normal central adiposity (OR=2.234; 95%CI=1.116–4.279). Results suggest that CRF relates to MRS independently of central adiposity.
Keywords: aerobic capacity; waist circumference; obesity; metabolic syndrome; cardiovascular risk factors; youths